2015
DOI: 10.1097/won.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Tibial Nerve Stimulation in the Treatment of Lower Urinary Tract Symptoms and Its Impact on Health-Related Quality of Life in Patients With Parkinson Disease

Abstract: These findings suggest that TTNS is effective in the treatment of LUTS in patients with PD, reducing urgency and nocturia episodes and improving urodynamic parameters as well as symptom scores measured by the OAB-V8 and health-related quality-of-life scores measured by the ICIQ-SF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 23 publications
4
78
0
6
Order By: Relevance
“…A total of 1 study was evaluated for the treatment of urinary dysfunction in PD, and 1 trial not meeting inclusion criteria was excluded . See Table for recommendations.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…A total of 1 study was evaluated for the treatment of urinary dysfunction in PD, and 1 trial not meeting inclusion criteria was excluded . See Table for recommendations.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The 13 papers reported 10 RCTs and 3 prospective cohort studies . Included studies were published between 2002 and January 2017 with 9 of the 10 trials and 2 of the 3 prospective observational studies published since 2009.…”
Section: Resultsmentioning
confidence: 99%
“…24 In another study it was reported that TTNS is effective in the treatment of LUTS in patients with PD, reducing urgency and nocturia episodes and improving urodynamic parameters as well as symptom scores measured by the OAB-V8 and health-related quality-of-life (HRQOL) scores measured by the ICIQ-SF. 25 BTX has been demonstrated in pilot and pivotal trials to be quite effective in reducing idiopathic OAB and NDO symptoms. 26 Anderson et al reported 100 IU injections of BTX as an office procedure with NDO due to PD.…”
Section: Page 9 Of 14mentioning
confidence: 99%